ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø£ØºÙ†ÙŠÙ‘Ø© Ø§Ù„ÙØµÙŠØØ© ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù…Ù† Ø¨Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© "Ø¨ÙˆÙˆØ§Ù†Ø§" ÙˆÙŠØ¯ÙˆØ±Ùˆ ÙˆØ§Ø±Ùˆ Ø³ÙŠØ¯ÙˆØ£Ø±Ø¬Ùˆ - muhammad rizal rizqi (Al-Fakkaar, 2023)
Vocabulary was an important element of language so that it included the meanings and use of words in the language from the speaker himself or from the writer. And the person will increase his skill in the language if he increases his vocabulary because the efficiency of the skill of the person's language is consistent with the vocabulary that he absorbed. Teaching Arabic needed to use the educational strategy to help the teacher teach vocabulary related to the study subjects, including song, and this is a new strategy. The use of song in teaching Arabic has two parts: the first, singing by learning and the second, learning by singing. The use of singing in teaching vocabulary removes boredom in learning and gives pleasure to students and develops vocabulary or increases vocabulary and facilitates them in memorizing vocabulary. This research aims to obtain an experimental evolutionary description: (1) to find out how to apply vocabulary teaching with eloquent song to students in the eighth grade of the junior high school â€œBuanaâ€ Wedoro Waru Sidoarjo (2) to find out the effectiveness of teaching vocabulary with eloquent song to students in the eighth grade at the junior high school â€œBuanaâ€ Wedoro Waru Sidoarjo. In this research methodology, the researcher uses quantitative research in teaching vocabulary using the song, and the research design is an experimental development study that experiments with the use of the song. This research consists of: plan design, application, observation and evaluation. The results of the research reached by the researcher are that the application of teaching vocabulary song eloquent value effectiveness result of "T" = 10.61 more than 2.01 / 2.75 p e 0 return any e 1 acceptable or that the hypotheses of the research is acceptable